2020
DOI: 10.1007/s10639-020-10332-y
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the differentiation practices of virtual school teachers

Abstract: Despite a large increase in enrollments of students in online courses at the K-12 level, there is very little research on the use of differentiation in fully online (called "virtual") schools. This study asked virtual teachers from two different types of schools to discuss their differentiation practices, and compared differentiation practices of teachers across these schools. Nineteen focus groups consisting of 92 teachers were conducted. Data were analyzed using Tomlinson's differentiation framework. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
1
12
0
1
Order By: Relevance
“…It is important to acknowledge that the time pressure to move online in 2020 may have impacted PSTs perceptions about the challenges of teaching and differentiation online, as teachers did not have time to learn and implement effective online learning. While this PST perception may have been influenced by the unique context of COVID-19, these findings do align with similar findings from Beck and Beasley (2020), who reported that teachers struggle to find ways to differentiate content, product and process for online learning. Difficulties in differentiating activities may have been related to PST indicating that they felt they needed to have the entire unit developed and online before students started working on it.…”
Section: Discussionsupporting
confidence: 86%
“…It is important to acknowledge that the time pressure to move online in 2020 may have impacted PSTs perceptions about the challenges of teaching and differentiation online, as teachers did not have time to learn and implement effective online learning. While this PST perception may have been influenced by the unique context of COVID-19, these findings do align with similar findings from Beck and Beasley (2020), who reported that teachers struggle to find ways to differentiate content, product and process for online learning. Difficulties in differentiating activities may have been related to PST indicating that they felt they needed to have the entire unit developed and online before students started working on it.…”
Section: Discussionsupporting
confidence: 86%
“…Virtual schools differ one from another also in the number and goals of the courses offered to students. In some virtual schools, students study one or two enrichment courses (Smith et al, 2005 ), whereas in other schools, students participate in online learning programs to earn academic credit for graduation or promotion to the next educational level (Beck & Beasley, 2021 ). There is evidence that distance education facilitates quality learning, improves student achievements, self-regulation, higher order thinking, collaboration, and technological skills (Barbour & Reeves, 2009 ; Cleveland-Innes & Garrison, 2021 ; Miron & Gulosino, 2016 ; Posey et al, 2010 ).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Moreover, the need to invest in infrastructure as well as to improve teachers' ICT competencies and the learning environment became obvious (Schuknecht and Schleicher, 2020). Thus, it is not surprising that current research shows that teachers rarely make use of ICT during ERT, and teachers rarely differentiated their instruction to address students' individual learning needs (Schwab et al, 2015;Beck, 2017, 2021;König et al, 2020;Letzel et al, 2020a;Beck and Beasley, 2021;Bond, 2021;Thorell et al, 2021). In a systematic review, Bond (2021) report that the most frequently used technologies were synchronous collaboration tools (e.g., live video lessons), knowledge organization and sharing tools (e.g., Google Classroom), text-based tools (e.g., WhatsApp, email), and multimodal production tools (e.g., recorded videos).…”
Section: In Online Teaching and Learning Contextsmentioning
confidence: 99%
“…Differentiated learning supported by technology has considerable potential (Beck and Beasley, 2021). On the one hand, it helps teachers to differentiate their instruction in a more flexible way by making teaching and learning more accessible for heterogeneous student populations (Cumming, 10.3389/feduc.2022.969737 Frontiers in Education 04 frontiersin.org 2014; Schwab et al, 2020;Demski et al, 2021).…”
Section: In Online Teaching and Learning Contextsmentioning
confidence: 99%